1996
DOI: 10.1111/j.1468-2435.1996.tb00527.x
|View full text |Cite
|
Sign up to set email alerts
|

The Economic Determinants of Greek Return Migration to the Islands of the East Aegean

Abstract: "The purpose of this article is to investigate the economic determinants of Greek return migration to the islands of the East Aegean, a region comprising hundreds of islands of different size in four administrative departments....[It] examines the sensitivity of return migration flows to changes in economic variables which influence decisions to return....The purpose...is to investigate the effect on return migration not only of economic development in the host country (push factors) but also of economic devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
3
0
1
Order By: Relevance
“…It has been reported that return migration is negatively related to the economic development in the host country (Lianos, 1980;Glytsos, 1991). Furthermore, Robolis & Xideas (1996) have observed that the variance of the return migration flow is determined by a combination of income and employment opportunities in both the host country and the country of origin. It can be argued from the results in this paper that economic conditions in South Africa and employment prospects in Zimbabwe (that would ordinarily favour skilled migrants) are likely to play a major role in influencing the return migration decision.…”
Section: Determinants Of Return Migration Intentionsmentioning
confidence: 99%
“…It has been reported that return migration is negatively related to the economic development in the host country (Lianos, 1980;Glytsos, 1991). Furthermore, Robolis & Xideas (1996) have observed that the variance of the return migration flow is determined by a combination of income and employment opportunities in both the host country and the country of origin. It can be argued from the results in this paper that economic conditions in South Africa and employment prospects in Zimbabwe (that would ordinarily favour skilled migrants) are likely to play a major role in influencing the return migration decision.…”
Section: Determinants Of Return Migration Intentionsmentioning
confidence: 99%
“…) 19 . Fairly recent empirical investigations of return migration to Greece (again mostly concerning return from Germany) have focused primarily on the economic variables of standard push-pull factors (Robolis, Boules, Souri and Pasadis 1989;Robolis and Xideas 1990;Glytsos 1991). As such they follow previous surveys (Lianos 1975;Bernard and Comitas 1978;Fakiolas 1980;Mousourou and Kollarou 1980;Papademetriou 1985;Unger 1986), with the exception of Bernard and AshtonVouyoucalos (1976) who used life histories from fifteen migrants and their families who had returned to Greece from Germany.…”
Section: Theorisation Of Return Migrationmentioning
confidence: 99%
“…Another issue worth considering is that of the reasons behind the return to the place of origin (Callea, 1986;Bessy and Riche, 1993;Dikaiou, 1994;Robolis and Xideas, 1996;Waldorf, 1997;Tunali, 1997;Kulu, 1998;Sayad, 1998).…”
Section: Introductionmentioning
confidence: 98%